Supercapacitors: Carbon-Based Nanostructures for Supercapacitor Application - Mishra S.; Mishra A.K. (My University, 2025)
The ever-increasing global energy demand and finite fossil fuel resources pose a great challenge to the scientific community to seek sustainable and renewable energy supply. The development of proficient electronic devices strongly depends on attaining high-energy density, large power density along with sustained cycle life. In this regard, supercapacitors show great possibilities in new-generation electronic devices and systems. The carbon nanostructures (activated carbon, carbon nanotubes and graphene or reduced graphite oxide) have been extensively investigated as competent electrode material due to their unique hierarchical structure, high surface area, meso-porosity, and excellent electrical and mechanical properties. This chapter thoroughly discusses the design and fabrication of high-performance supercapacitors based on carbon nanomaterials have been comprehended. First, the authors elucidate the involved charge-storage mechanisms of carbon-based supercapacitors followed by a brief description of factors influencing electrochemical performance. Then, different designing concepts of carbon nanocomposite-based supercapacitors are summarized for various wearable electronics. © 2024 selection and editorial matter, Piyush Kumar Sonkar and Vellaichamy Ganesan; individual chapters, the contributors.